Insecticidal activity guided isolation of palytoxin from a red alga, Chondria armata. Issue 32 (10th August 2016) - Mori, Shoko; Sugahara, Kohtaro; Maeda, Mitsuru; Nomoto, Kyosuke; Iwashita, Takashi; Yamagaki, Tohru
Graphical abstract: Highlights: Palytoxin was isolated from a marine red alga, Chondria armata . The compound from the alga showed lethal activity at 5 ng against cockroaches. The previously reported NMR signal assignment of palytoxin was refined. Abstract: A red alga, Chondria armata, was used as a vermifuge in Japan. Previously, we isolated domoic acids from C. armata guided by the insecticidal activity against American cockroaches. Further investigations led to the discovery of a compound one-thousand times more toxic than domoic acid. It showed lethal activity at 5 ng against cockroaches. The insecticidal compound was identified as palytoxin by means of NMR and MS. Careful interpretation of the NMR spectra allowed us to refine the previously reported NMR assignment of palytoxin. Palytoxin has been isolated from various organisms, and it is significant that palytoxin was isolated from marine plants.